2010
DOI: 10.1097/mcg.0b013e3181bd885e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep on Excessive Belching

Abstract: Supragastric belch is the prominent belching pattern in patients with excessive belching. Supragastric belches almost ceased at night suggesting the presence of a behavioral disorder. There were no diurnal changes in the rate of gastric belches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
2
18
0
2
Order By: Relevance
“…The patients who did respond also gave a specific history of belching, such that it was chronic, generally persisted throughout the day without relation to eating, resolved during sleep, and improved during exercise. These patients do not typically belch during sleep because of lack of swallowing. In contrast, a lack of belching during exercise most likely results from the need for concentrated open mouth breathing during exercise that both inhibits and does not allow time for swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…The patients who did respond also gave a specific history of belching, such that it was chronic, generally persisted throughout the day without relation to eating, resolved during sleep, and improved during exercise. These patients do not typically belch during sleep because of lack of swallowing. In contrast, a lack of belching during exercise most likely results from the need for concentrated open mouth breathing during exercise that both inhibits and does not allow time for swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Th is suggests that in the majority of patients markedly excessive belching is likely related to supragastric belching ( 71 ). Identifi cation of supragastric belching with intraluminal impedance has also allowed for the development of eff ective therapies, most notably baclofen and diaphragmatic breathing (72)(73)(74).…”
Section: Intraluminal Impedance In Belching and Rumination Syndromementioning
confidence: 98%
“…Recession of SGB during sleep, speech and distraction, as well as the type of muscles that are included in its pathogenesis are suggestive of the behavioural nature of the disease. 7,9 Hence, interest is mainly focused in behavioural therapies. Speech therapy has been applied in a recent pilot study with 11 patients and showed positive results.…”
Section: Discussionmentioning
confidence: 99%